2005
DOI: 10.1161/01.hyp.0000161990.98383.ad
|View full text |Cite
|
Sign up to set email alerts
|

High-Salt Diet Inhibits Expression of Angiotensin Type 2 Receptor in Resistance Arteries

Abstract: Abstract-Recent studies suggested that type 2 angiotensin receptor (AT2R) could contribute to regulation of blood pressure and/or vascular remodeling. A key question relates to the effects of potential modulators of vascular AT2R expression. In the present work, we evaluated if high salt intake (70 mmol/L NaCl in drinking water) could modulate rat mesenteric artery AT2R function and expression. Angiotensin II dose-response curves were studied in rat perfused pressurized small-diameter arteries in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 67 publications
1
20
1
Order By: Relevance
“…13,14 External artery diameter was determined by videomicroscopy. Vasodilatory responses to shear stress were measured according to Matrougui et al 15 Isometric tension studies were performed according to Rahman et al.…”
Section: Contractility Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 External artery diameter was determined by videomicroscopy. Vasodilatory responses to shear stress were measured according to Matrougui et al 15 Isometric tension studies were performed according to Rahman et al.…”
Section: Contractility Studiesmentioning
confidence: 99%
“…Kidney and mesenteric arteries were processed for total RNA extraction, 14 and PCRs were carried out with specifics primers for rat ENaC subunits.…”
Section: Rt-pcrmentioning
confidence: 99%
“…High salt diet has been shown to inhibit the expression of AT2r [86] and it is proposed that EGF release from its precursor via mechanotransduction is less efficient in the presence of high salt intake. The inhibition of Pathway 1 leads to the dominance of Pathway 2 (AT1r).…”
Section: Salt and Aldosteronementioning
confidence: 99%
“…It has been demonstrated that the renin-angiotensin (RAS) is important in the development and maintenance of hypertension in both essential hypertensive patients and animal models of hypertension [5,6] . Moreover, many studies have revealed that high salt could stimulate the RAS and induce angiotensin II receptor 1 (AT 1 R) overexpression, which may be responsible for the elevation of blood pressure [7,8] . The blockade or interruption of RAS by pharmacological agents, such as the angiotensin-converting enzyme inhibitor and AT 1 R antagonists, have been extremely successful in the treatment of hypertension and the prevention of it complications.…”
Section: Introductionmentioning
confidence: 99%